Generalized Disappointment Aversion, Long-run Volatility Risk, and Asset Prices - Bonomo, Marco; Garcia, René; Meddahi, Nour; Tédongap, Roméo (Review of Financial Studies, 2011)
[We propose an asset pricing model with generalized disappointment aversion preferences and long-run volatility risk. With Markov switching fundamentals, we derive closed-form solutions for all returns moments and predictability regressions. The model produces first and second moments of price-dividend ratios and asset returns as well as return predictability patterns in line with the data. Compared to Bansal and Yaron (2004), we generate (i) more predictability of excess returns by price-dividend ratios; (ii) less predictability of consumption growth rates by price-dividend ratios. Our results do not depend on a value of the elasticity of intertemporal substitution greater than one.]